Psychological Symptoms and Behavioral Changes in Children and Adolescents During the Early Phase of COVID-19 Quarantine in Three European Countries - Francisco, Rita; Pedro, Marta; Delvecchio, Elisa; Espada, Jose Pedro; Morales, Alexandra; Mazzeschi, Claudia; Orgilés, Mireia (Frontiers in Psychiatry, 2020)
The COVID-19 pandemic forced the home confinement of the majority of population around the world during several weeks of 2020, including a significant number of children and adolescents. Negative psychological effects have been identified in adults, but research about the impact of this type of social-distancing measure on children and adolescents is scarce. The present study aimed to describe and compare the immediate psychological and behavioral symptoms associated to COVID-19 quarantine in children and adolescents from three southern-European countries with different levels of restrictions (Italy, Spain and Portugal). Participated in the study parents of 1480 children and adolescents (52.8% boys) between 3 and 18 years-old (M = 9.15, SD = 4.27). An online survey using snowball sampling techniques was conducted during 15 days between March and April 2020, the early phase of the quarantine associated to COVID-19 outbreak. Parents answered questionnaires about sociodemographic data, housing conditions, immediate psychological responses during quarantine (e.g., anxiety, mood, sleep, behavioral alterations), patterns of use of screens, daily physical activity, and sleep hours before and during the quarantine. Results revealed an increase in children's psychological and behavioral symptoms, higher use of screen-time, lower physical activity and more sleep hours/night. Italian children presented less psychological and behavioral symptoms compared to Portuguese and Spanish children. In general, hierarchical multiple regressions revealed that having an outdoor exit in the house (e.g., garden, terrace) contributed to lower levels of psychological and behavioral symptomatology. Future studies are needed to identify family and individual variables which can better predict children and adolescents’ wellbeing during and after quarantine. Recommendations for families and implications for practice are discussed.